2012
DOI: 10.4025/actasciagron.v34i4.12333
|View full text |Cite
|
Sign up to set email alerts
|

Use of complex supplements and light-differential effects for micropropagation of Hadrolaelia purpurata (= Laelia purpurata) and Encyclia randii orchids

Abstract: ABSTRACT. In the current study, complex (coconut water and ripe-banana pulp) and specific (micronutrients, peptone and activated charcoal) supplements were added to Knudson-C medium (KC) medium to stimulate the in vitro propagation of Hadrolaelia purpurata (=Laelia purpurata) and Encyclia randii orchid species. The highest number of H. purpurata seedlings occurred in KC medium containing 90 g L -1banana pulp maintained with 24-hour illumination. Positive effects of the banana pulp addition in KC medium were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
1
Order By: Relevance
“…This is in agreement with Arditti (1992) who proposed that for in vitro growth of PLBs and seedling of an orchid, some complex additives were satisfactory, while some were unsatisfactory and even inhibitory. Goncalves et al (2012) found that the highest number of seedlings of Laelia purpurata orchid occurred in Knudson C (KC) medium containing 90 g L -1 banana pulp, while the seedling number of Encyclia orchid was high in KC medium containing coconut water. Other research by Nambiar et al (2012) investigated that the best organic additive for proliferation of PLBs of Dendrobium Alya Pink was coconut water compared to banana and tomato homogenate.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with Arditti (1992) who proposed that for in vitro growth of PLBs and seedling of an orchid, some complex additives were satisfactory, while some were unsatisfactory and even inhibitory. Goncalves et al (2012) found that the highest number of seedlings of Laelia purpurata orchid occurred in Knudson C (KC) medium containing 90 g L -1 banana pulp, while the seedling number of Encyclia orchid was high in KC medium containing coconut water. Other research by Nambiar et al (2012) investigated that the best organic additive for proliferation of PLBs of Dendrobium Alya Pink was coconut water compared to banana and tomato homogenate.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various organic supplements studied (CW, PH, and BH), BH at a concentration of 25 or 50 g•L −1 improved shoot and root number and shoot and root length [48]. Gonçalves et al [49] found that the number of Hadrolaelia purpurata seedlings produced was the highest on KC medium containing 90 g•L −1 of BH. Furthermore, Utami and Hariyanto [50] observed the effect of supplementation with 150 mL•L −1 CW with different BH concentrations (0, 5, 10, 15 g•L −1 ) on the plantlet development of Phalaenopsis amboinensis and found that the organic supplementation of CW together with BH had significantly increased the growth of plantlets.…”
Section: Banana Homogenatementioning
confidence: 99%
“…It could be noted that Brazil has the highest number of published works both on propagation and germplasm conservation, while for some countries only researches referring to propagation of native orchid species are reported and for other countries (Guyana, Paraguay, Trinidad and Tobago, Suriname, Uruguay) there were no registered works in any of the topics. Almeida et al 2017;Caovila et al 2016;Cardoso and Ono 2011;Cavalcante Martini et al 2001;Corrêa Pereira et al 2011;2015;Da Silva et al 2014;Da Silva Júnior et al 2012;De Carvalho et al 2018;De Conti et al 2018;De Melo Ferreira et al 2017;De Menezes Gonçalves et al 2012;Dezan et al 2012;Dignart et al 2009;Dorneles and Trevelin 2011;Endres Júnior et al 2014;Favetta et al 2017;Galdiano Júnior et al 2011;2012a,b;Gomes de Araújo et al 2009;Hosomi et al 2017;Lando et al 2016;Lone et al 2010;Mantovani et al 2016;Massaro et al 2012;Monteiro do Rêgo et al 2009;Moraes et al 2005;Pasqual et al 2011;Pedroso-de-Moraes et al 2012;Pereira et al 2018;Pereira Gomes et al 2015;Prizão et al 2012;Rodrigues et al 2015;Rodrigues Guimarães et al 2013;Sasamori et al 2015;…”
Section: In Vitro Conservation Approaches In Orchidsmentioning
confidence: 99%